African Pentecostalism an introduction - Kalu, Ogbu. (Oxford ; New York : Oxford University Press, 2008)
In this book, Ogbu Kalu provides an overview of Pentecostalism in Africa. He shows the amazing diversity of the faith, which flourishes in many different forms in diverse local contexts, and demonstrates that African Pentecostalism is distinctly African in character, not imported from the West.
Precedents in early charismatic movements, 1900-1960s -- Oriki : genealogy and identity in Pentecostal historiography -- Bakuzufu : contested identities and the quest for power in African Christianity -- Moya : African charismatic initiatives and classical Pentecostal missionaries -- Mademoni : African-instituted churches in Pentecostal rhetoric -- The modern Pentecostal movement,1970s-1990s -- Aliliki : charismatic resurgence of the 1970s -- The big man of the big God : Pentecostalism, media, and popular culture in the 1980s -- Elijah's mantle : Pentecostal re-evangelization of Africa in the 1990s -- Gendered charisma : charisma and women in African Pentecostalism -- Pentecostalism in the African public space -- Sankofa : Pentecostalism in the African map of the universe -- Masters on horses : the roots of Pentecostal public ethics -- Tembisa : Pentecostal political theology and practices -- Child of the bondwoman : Islam and Sharia in Pentecostal rhetoric -- Pentecostal words and worlds -- Standing on the Word : Pentecostal theologies -- Reverse flow : Pentecostalism and immigrant African Christianity.
Includes bibliographical references (p. [321]-344) and index.
Description based on print version record.
Keywords: Pentecostalism -- Africa -- History; Africa -- Church history -- 20th century; Electronic books